Field and semi-field evaluation of Bacillus thuringiensis var. israelensis versus Temephos® in Aedes aegypti controlAvaliação de campo e simulado de campo de Bacillus thuringiensis var. israelensis versus Temephos® no controle de Aedes aegypti - Lima, Jose Bento Pereira; Goreti Rosa-Freitas, Maria; Melo Rodovalho, Cynara; Aparecida Braga, Ima (Journal of Health & Biological Sciences, 2016)
Introduction: Aedes aegypti is a vector of the important arboviruses worldwide. Vector control continues to rely mainly on fighting immature stages. Resistance to the larvicide Temephos® was detected in many regions of Brazil since 2000 what led control programs to search for alternative products, such as Bacillus thuringiensis var. israelensis (Bti). Caicó municipality (Rio Grande do Norte State, Brazil) was one of the first cities to use Bti. However, after some time, Bti low persistence was noticed as jeopardizing effective vector control. Objective: To compare the efficacy of two Bti granulate formulations, Vectobac G® and Vectobac WDG® and Temephos® against Ae. aegypti in field and semi-field conditions. Methods: Field tests were carried out in two neighbouring areas which presented Ae. aegypti infestation indices >3%: Walfredo Gurgel and Boa Passagem, Caicó, RGN, Brazil, in 2004. Semi- field tests were performed in the patio of a building. Results: For the field conditions, mortality rates >80% were maintained for 14 days, average. After nine weeks, positive containers for Ae. aegypti in the field were >10% in the area of application of Bti and <1% in the area where Temephos® was applied. In the semi-field conditions Ae. aegypti larval mortality >80% was maintained for up to 56 days for Temephos®, 35 days for Vectobac G® and 49 days for Vectobac WDG®. Conclusions: The results point out to low Bti persistence in the field, mainly for containers exposed to sunlight. Local climatic and environmental conditions should be regarded when new products are tested due to high regional variability prevailing in Brazil.